Financial Performance Under Pressure: The Moderating Effect of Corporate Social Responsibility on Economic Fluctuations (Evidence from China) - Xie, Yumeng; Kharuddin, Saira; Yusri, Yusniyati (Journal of Sustainable Competitive Intelligence, 2025)
Objective: This study aims to examine the effects of Corporate Social Responsibility (CSR) on the financial performance of A-share listed companies in China from 2015 to 2024, particularly assessing whether CSR can function as a financial stabilizer during periods of economic uncertainty. Methodology/Approach: A quantitative explanatory design was employed using panel data from 2,000 A-share companies. The analysis integrates data from the CSMAR, Hexun, and Bloomberg ESG databases, as well as China’s Economic Policy Uncertainty (EPU) index. Hierarchical and moderation regressions, alongside fixed effects and system-GMM estimations, were applied to ensure robustness. Subgroup and industry-level analyses were conducted to account for ownership and visibility heterogeneity. Originality/Relevance: The study uniquely integrates stakeholder, resource-based, signaling, legitimacy, and agency theories to conceptualize CSR as “resilience capital” under economic distress. Unlike traditional views of CSR as a reputational or ethical tool, this research positions CSR as a strategic financial mechanism within China’s hybrid institutional environment characterized by state dominance and market competition. Main Findings: CSR has a positive direct impact on financial performance (β = 0.154, p < 0.001) and significantly moderates the negative effect of economic policy uncertainty (β = 0.083, p < 0.01). This buffering effect is stronger in non-state-owned enterprises (β = 0.091, p < 0.01) and in industries with higher stakeholder visibility (β = 0.097, p < 0.01). CSR mitigates financial decline through innovation, information-signal, stakeholder-insurance, and financial-constraint channels. Theoretical/Methodological Contributions: This study advances CSR and sustainability literature by empirically validating a multi-channel moderation model and introducing a framework where CSR acts as a dynamic risk-mitigation and resilience-building capability. Methodologically, it contributes by employing advanced panel modeling, robustness checks, and 3D moderation visualizations—tools that can be replicated in future CSR–finance studies.